Cancer nurses’ perceptions of ethical climate in Greece and Cyprus - Cloconi, Constantina; Papastavrou, Evridiki; Charalambous, Andreas (My University, 2019)
Background: In recent years, the interest in ethical climate has increased in the literature. However, there is limited understanding of the phenomenon within the cancer care context as well as between countries. Aim: To evaluate cancer nurses’ perceptions of hospital ethical climate in Greece and Cyprus. Research design: This was a quantitative descriptive–correlational comparative study with cancer nurses. Data were collected with the Greek version of the Hospital Ethical Climate Survey questionnaire in addition to demographic data. Participants and research context: In total, n = 235 cancer nurses working in cancer care settings in Greece and Cyprus were recruited at two national oncology nursing conferences. Ethical considerations: The study conforms to the principles of the World Medical Association Declaration of Helsinki and the relevant ethical approvals were obtained according to national law. Results: The results showed that in terms of the “Managers” dimension, participants working in Greek hospitals (4.30 ± 0.73) had a higher score compared to the Cyprus participants (3.66 ± 0.93) (t = −5.777, p ≤ 0.001). The perceptions of nurses working in oncology units in Greece regarding the ethical climate were more positive compared to Cyprus (M = 3.67 for Greece and M = 3.53 for Cyprus, p ≤ 0.001). Nurses with a higher level of education had a lower average ethical climate score across all dimensions. All dimensions exhibit positive and moderate to high correlations between them (r = 0.414–0.728, p < 0.01). Conclusion: It is imperative to evaluate and improve the hospital ethical climate that prevails in each cancer care department. This highlights the fact that nurses working in seemingly similar cultural and organizational contexts might still have different perceptions of the ethical climate. Despite these differences, it is necessary to create the right conditions to address ethical issues. A positive ethical climate requires good relationships between healthcare professionals and the presence of good teamwork in order to ensure better healthcare provision.
Keywords: Climate; Ethics; Hospital ethical climate; Nurses; oncology